VLORA`S WOMEN AND CERVICAL CANCER HEALTH BELIEFS - Kamberi, Fatjona; Theodhosi, Gjergji; Ndreu, Vjollca; Sinaj, Enkeleda; Cuberi, Diana; Kamberi, Leonard (European Scientific Journal, ESJ, 2015)
Cancer in general in Albania is an increasing problem and cervical cancer is the third most common gynecologic cancer among all women. Refer to European Code Against cancer an important action for women to help to prevent cervical cancer is to take part in organised cancer screening programmes. The study aims to identify in women health beliefs about cervical cancer. This is a transversal and analytical study with a sample of 210 healthy women from Vlora city with different socio-economic and educational levels. A selfadministered questionnaire that assesses the health beliefs components about cervical cancer was the data collection instrument. The results highlighted low risk perception relative to cervical cancer. Most of women believe that cervical cancer as dangerous as all the other cancers and uncertainties about the chances to recover from it exist among them. Misunderstandings and high sensitivity relate to cervical screening. Relationship between perceived benefits, emotional, economic barriers and Pap test uptake was found. Large numbers of women never screened. The results indicated that to improve the women's attitudes to health, to encourage adherence to cervical screening and to avoid misconceptions due to lack of information conversations with health operators and the designing of effective prevention strategies based on health beliefs are fundamental.